Purification of Recombinant Human Pretrombin-2 in Escherichia coli for Thrombin Production as Fibrin Glue Components - Saronom Silaban; Iman Permana Maksum; Khomaini Hasan; Sutarya Enus; Toto Subroto; Soetijoso Soemitro (Pascasarjana Universitas Negeri Medan, 2017)
Abstract: Pretrombin-2 (PT2) is a thrombin precursor that plays a role in converting fibrinogen to fibrin for the process of wound recovery. This material can be applied instead of eye surgery suture technique. The intein-mediated refining system to purify the protein is attractive to be developed, since the protein is obtained by one purification step, capable of self-splicing, the protein can be diffused in to the N-terminal (PT2 cutting of the intein induced marker changes in pH and temperature) and on the C-terminal (cutting PT2 from the intein-induced marker of the thiol reagent). In this study, we purified the PT2 fusion of the expression of E. coli BL21 (DE3) Arctic Express in the intein-mediated chitin matrix column. PT2 was fused with a tag at its N-terminal position, containing the sequence of intein codes SspDnaB followed by chitin binder domain (CBD). Furthermore, the PT 2 fusion was expressed on the E. coli host, then purified in the chitin matrix column. The PT2 cutting process of the intein marker induced changes in the pH and temperature in the column. PT2 fusion was successfully purified in the intein-mediated chitin matrix. The PT2 fusion cut from the induced intein buffer marker at pH 6.5 and incubation at the temperature of 25 oC for 48 hours.Keywords: E. coli, expression, intein mediated purification, pH and temperature changes, PT2